Interindividual variation of progesterone elevation post LH rise: implications for natural cycle frozen embryo transfers in the individualized medicine era - Carol Coughlan; Baris Ata; Raquel Del Gallego; Barbara Lawrenz; Laura Melado; Suzan Samir; Human Fatemi (Reproductive Biology and Endocrinology, 2023)
Abstract Background The key to optimal timing of frozen embryo transfer (FET ) is to synchronize the embryo with the receptive phase of the endometrium. Secretory transformation of the endometrium is induced by progesterone. In contrast, detection of the luteinizing hormone (LH) surge is the most common surrogate used to determine the start of secretory transformation and to schedule FET in a natural cycle. The accuracy of LH monitoring to schedule FET in a natural cycle relies heavily on the assumption that the period between the LH surge and ovulation is acceptably constant. This study will determine the period between LH rise and progesterone rise in ovulatory natural menstrual cycles. Methods Retrospective observational study including 102 women who underwent ultrasound and endocrine monitoring for a frozen embryo transfer in a natural cycle. All women had serum LH, estradiol and progesterone levels measured on three consecutive days until (including) the day of ovulation defined with serum progesterone level exceeding 1ng/ml. Results Twenty-one (20.6%) women had the LH rise 2 days prior to progesterone rise, 71 (69.6%) had on the day immediately preceding progesterone rise and 10 (9.8%) on the same day of progesterone rise. Women who had LH rise 2 days prior to progesterone rise had significantly higher body mass index and significantly lower serum AMH levels than women who had LH rise on the same day with progesterone rise. Conclusion This study provides an unbiased account of the temporal relationship between LH and progesterone increase in a natural menstrual cycle. Variation in the period between LH rise and progesterone rise in ovulatory cycles likely has implications for the choice of marker for the start of secretory transformation in frozen embryo transfer cycles. The study participants are representative of the relevant population of women undergoing frozen embryo transfer in a natural cycle.